Karaktristik proses destilasi asap cair grade 3 - Kemas Ridhuan; Tri Cahyo Wahyudi; Danang Sulistiyo; Bahtera Anggara (TURBO [Tulisan Riset Berbasis Online], 2021)
Distillation of liquid smoke is a process of heating liquid smoke based on the difference in its boiling point and then cooled to get liquid smoke with better quality. This heating aims to separate unwanted components in liquid smoke such as tar and benzopyrene. The process is strongly influenced by several things such as temperature and distillator. From these two measurements, several characteristics such as heating rate, distillation flow rate of liquid smoke, production capacity, heating temperature, steam temperature and distillation time, as well as the characteristics of the resulting liquid smoke can be known.The purpose of this study is to determine the characteristics of the 3rd grade liquid smoke distillation process with electric heating and water cooling condenser which includes the production capacity of liquid smoke and to determine the quality and quantity of liquid smoke, heating rate, electricity consumption, flow rate and to determine the efficiency of 2nd grade liquid smoke production.This research was conducted at the Laboratorium Teknik Mesin Universitas Muhammadiyah Metro, this study used a distillation apparatus made of Aluminium plate 1 mm thick, 180 mm in diameter, 250 mm high. Condenser with 0.5 inch diameter copper pipe 3,5 m long, 3 inch diameter PVC pipe, 3m long. The raw material for 3rd grade liquid smoke is 3 liters.The results obtained that the distillation apparatus has a capacity of 3 liters, the distillation temperature affects the rate of heating that occurs, namely the distillation temperature of 110oC, the heating rate is 707,42 J/second, the electricity consumption is 4,48kWh, the time is 45 minutes, and for a temperature of 120 oC the heating rate is 754,60 J/second, electricity consumption is 4,467 kWh in 65 minutes. The highest yield of liquid smoke is at a temperature of 110 oC, which is 2840 ml with a flow rate of 8,35 ml/minute and an efficiency of 94,6%, pH level of 2,15. And for a temperature of 120 oC it produces 2560 ml of liquid smoke, with a flow rate of 8,67 ml/minute and an efficiency of 85,3%, with a pH level of 2,10.